Strategies for the engagement of youth in health-related activities in Portugal: the CO-CREATE project - Mendes, Sofia (2023)
Introduction: The lack of attention paid by policymakers to the views and role of young people in societal matters, including health, has been a contributor factor for the poor youth involvement in the development of health-related policies. The CO-CREATE (CC) project aims to collaborate with adolescents across Europe in developing policy ideas that contribute to overweight and obesity prevention. Aim: Present the strategies for the recruitment and engagement of youth in CC project in Portugal. Methods: In order to recruit for a diversity of youths, the Portuguese CC Team identified the scout organization CNE (Corpo Nacional de Escutas) as the most relevant gatekeeper, being the biggest Portuguese youth association. The principles of youth-led participatory action research were employed to design 3 Youth Alliances, temporal gathering of a group of young people that work together towards a common goal: Scout groups of Oeiras, Parque das Nações and São Domingos de Rana. Results: Several opportunities were created to promote the Portuguese youth engagement in the project such as the planning and organization of local and national Dialogue Forums and the presentation of youth policy ideas to three political parties of the Portuguese Parliament. Recommendations from the CC youth for encouraging youth involvement in the development of policies are highlighted below: - Promote training and empower youth, for example, through and in schools; - Create opportunities for youth to be part of national and international projects as active partners is needed, and facilitating youth promoting this via their channels; - Establish partnership with existing youth organizations to foster synergies; - Use tools that ensure equal and balanced participation in discussions between youth and stakeholders. Conclusion: Nowadays young people’s voices remain underrepresented in health policy processes, however CC is an example of a successful initiative that was able to motivate and mobilize youth in Portugal.